Highly efficient noble metal free copper nickel oxysulfide nanoparticles for catalytic reduction of 4-nitrophenol, methyl blue, and rhodamine-B organic pollutants. (5th June 2017) - Abay, Angaw Kelemework; Chen, Xiaoyun; Kuo, Dong-Hau
Abstract : Novel and noble metal-free copper nickel oxysulfide nanoparticles have been successfully fabricated by using a simple, cost-effective, and eco-friendly solution-based approach, with copper oxysulfide as a comparative. Abstract : In this study, novel and noble metal-free copper nickel oxysulfide (CuNiOS) nanoparticles have been successfully fabricated by using a simple, cost-effective, and eco-friendly solution-based approach, with copper oxysulfide (CuOS) as a comparative. The CuOS and CuNiOS catalysts with various Ni contents were investigated by different techniques. The catalytic activities of the samples were assessed by the catalytic reduction of organic dyes such as 4-nitrophenol (4-NP), methylene blue (MB), and rhodamine-B (RhB) together with NaBH4 in an aqueous solution. The results obtained from ultraviolet-visible (UV-vis) spectroscopy indicated that CuNiOS-0.6 prepared with a Cu : Ni precursor mole ratio of 1 : 0.6 had the best catalytic performance for the reduction of 4-NP, MB, and RhB in comparison to the other CuNiOS catalysts and the monometallic catalyst (CuOS) due to synergistic effects. In addition, the CuNiOS-0.6 catalyst is also better than other CuNiOS ones due to the presence of optimum amounts of Ni in the CuNiOS sample. Thus, the present approach provides a promising way to fabricate different noble metal free bimetallic oxysulfide catalysts for extensive applications in catalysis and reduction/removal of other organic pollutants.